2019
DOI: 10.1007/s12308-019-00350-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets and microenvironment in sequential biopsies of classical Hodgkin lymphoma at diagnosis and relapse

Abstract: Classical Hodgkin lymphoma is dominated by the non-neoplastic microenvironment, while the neoplastic Hodgkin-Reed-Sternberg cells compose only a minority of cells in the lymphoma tissue. Both the Hodgkin-Reed-Sternberg cells due to their expression of CD30 and PD-L1 and the microenvironment with abundant T cells and expression of PD1 are specifically targeted by new treatment concepts. We aimed to understand the dynamics of therapeutic targets in patients treated with conventional chemotherapy. We analyzed seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Of note, the alteration in PD1/PD-L1 expression in the tumor microenvironment seems to be specific for relapses under anti-PD1 treatment and has not been observed in relapses after conventional therapy. 13,29,32 It remains unknown whether the observed disturbance in the microenvironment with respect to PD1/PD-L1 reflects HRSCs being less competent in modeling the microenvironment or less dependent on the specific microenvironmental composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the alteration in PD1/PD-L1 expression in the tumor microenvironment seems to be specific for relapses under anti-PD1 treatment and has not been observed in relapses after conventional therapy. 13,29,32 It remains unknown whether the observed disturbance in the microenvironment with respect to PD1/PD-L1 reflects HRSCs being less competent in modeling the microenvironment or less dependent on the specific microenvironmental composition.…”
Section: Discussionmentioning
confidence: 99%
“…The average value of 2 independent fields of view was calculated as previously described. 13 Expression of b2-microglobulin and HLA-DP was scored by counting the number of HRSCs in the high-power field with membrane or cytosolic staining, as previously described. 2 Samples were defined as positive if the majority of HRSCs had membrane staining, they were defined as negative if no HRSC had membrane staining, they were defined as partially positive if only a few HRSCs had membrane staining, and they were defined as cytoplasmic only if only cytoplasmic staining was observed.…”
Section: Immunohistochemistry and Digital Whole-slide Image Analysismentioning
confidence: 99%
“…Genes downregulated at diagnosis in r/r cHL patients compared to non-r/r patients were mostly related to B-cell differentiation or activation. Among them, CD79A, MS4A1, CD74, CD81 genes have already been identified as favorable prognosis factors in cHL patients [20][21][22][23][24]. Indeed, it has been demonstrated that loss of B-lineage identity allows HRS cells to survive in the absence of BCR signaling, and prevents the induction of apoptosis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…We examined the immune checkpoints expression and the number of TAMs in a cohort of 15 patients with primary and in repeated samples after immunotherapy failure and found the enrichment of PD-1-positive and LAG-3-positive cells and depletion of TAMs (CD163, CD68-positive cells). In previously published studies, several researchers found increasing levels of PD-1-positive T cells in cHL at relapse after standard chemotherapy by the immunohistochemical method [ 61 ], while in other reports, changes in PD-1-positive cell counts at relapse were not found by immunohistochemical or gene expression analysis [ 62 , 63 ]. In the analysis of the specimens at relapse in patients receiving standard chemotherapy, Schnitter et al found no evidence of enrichment of TAMs (CD163-positive cells) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies, several researchers found increasing levels of PD-1-positive T cells in cHL at relapse after standard chemotherapy by the immunohistochemical method [ 61 ], while in other reports, changes in PD-1-positive cell counts at relapse were not found by immunohistochemical or gene expression analysis [ 62 , 63 ]. In the analysis of the specimens at relapse in patients receiving standard chemotherapy, Schnitter et al found no evidence of enrichment of TAMs (CD163-positive cells) [ 62 ]. The expression markers or cell composition may change when patients receive immunotherapy.…”
Section: Discussionmentioning
confidence: 99%